Molecular detection and characterization of noroviruses in river water in Thailand. (4th February 2016) - Inoue, K.; Motomura, K.; Boonchan, M.; Takeda, N.; Ruchusatsawa, K.; Guntapong, R.; Tacharoenmuang, R.; Sangkitporn, S.; Chantaroj, S.
Abstract: Norovirus (NoV) generally exists as a mixture of multiple genotype variants in nature. However, there has been no published report monitoring NoV in natural settings in Thailand. To obtain information on mixed presence of the NoV RNA genome, we conducted viral genome analysis of 15 water specimens collected from five sites in a river near Bangkok between August 2013 and August 2014. The number of viral RNA copies per specimen declined progressively from the most upstream to the most downstream site. Following direct nucleotide sequencing of the PCR products, we obtained three partial genome sequences of the NoV GI strain and 13 partial genome sequences of the NoV GII strains. Phylogenetic analysis indicated the presence of four GII.4 variant groups pro‐circulated after the Den Haag_2006b, New Orleans_2009 and Sydney_2012 outbreaks. On the other hand, only GI.4 was observed from the specimens collected on April, 2014. These results indicated that multiple genogroups and genotypes of noroviruses are present and are circulating in the natural environment in Thailand as in other countries. Our study provides comprehensive information on the occurrence of new variants. Significance and Impact of the Study: Our study is the first paper that multiple genogroups and genotypes of norovirus exist, and are circulating in the river water near Bangkok, Thailand. Phylogenetic analysis indicated the presence of four GII.4 variant groups pro‐circulated after the Den Haag_2006b, New Orleans_2009 and Sydney_2012 that caused outbreaks in the world. Continued research will be essential for understanding the natural history of NoV and the control of future outbreaks. Abstract : Significance and Impact of the Study: Our study is the first paper that multiple genogroups and genotypes of norovirus exist, and are circulating in the river water near Bangkok, Thailand. Phylogenetic analysis indicated the presence of four GII.4 variant groups pro‐circulated after the Den Haag_2006b, New Orleans_2009 and Sydney_2012 that caused outbreaks in the world. Continued research will be essential for understanding the natural history of NoV and the control of future outbreaks.